2021
DOI: 10.35691/jbm.1202.0208
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of the Effects of Bioactive Compounds of the Ethanolic Extract of Ramalina Farinacea (Ramalinaceae) on the Development, Eating and Pupation Behavior of Drosophila Melanogaster (Diptera: Drosophilidae)

Abstract: Plants are rich in bioactive chemical secondary metabolites and have proven insecticidal activity by killing or repelling insects. In this work, we aim to evaluate the direct and delayed effects of ethanolic plant extracts on the vinegar fly (Drosophila melanogaster). The treatment was performed by ingestion on second instar larvae (L2) to evaluate the impact of the ethanolic extract on development for 15 days and subsequently on the feeding behavior of the larvae. The results of this study indicate a slowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Drosophila is polyphagous pests attacking a wide range of fruits, which may have facilitated their spread in different regions (Boughdad et al, 2021;Cini et al, 2014;Pfeiffer et al, 2019;Zanuncio-Junior et al, 2018). In Algeria, Drosophila are known for their pests of different types of fruit tree in particularapple fruit tree Malus domestica at Annaba (northeast of Algeria) and pomegranate fruit tree Punica granatum at M'sila (The central part of Algeria) (Khaldi et al, 2021;Rahat et al, 2021). In this study, we found that they attack the apricot, fig and grapes fruits.…”
Section: Discussionmentioning
confidence: 58%
“…Drosophila is polyphagous pests attacking a wide range of fruits, which may have facilitated their spread in different regions (Boughdad et al, 2021;Cini et al, 2014;Pfeiffer et al, 2019;Zanuncio-Junior et al, 2018). In Algeria, Drosophila are known for their pests of different types of fruit tree in particularapple fruit tree Malus domestica at Annaba (northeast of Algeria) and pomegranate fruit tree Punica granatum at M'sila (The central part of Algeria) (Khaldi et al, 2021;Rahat et al, 2021). In this study, we found that they attack the apricot, fig and grapes fruits.…”
Section: Discussionmentioning
confidence: 58%